Pengembangan Soft Skill Melalui Pembelajaran IPA SD/MI di Era Society 5.0 - Miah, Mazrikhatul (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Science learning in SD/MI is one of the initial stages that forms the basis for shaping character and determining one's success in the future. The challenge of education is currently entering the era of society 5.0, where humans must live side by side in harmony with information technology that is developing rapidly in the 4.0 era. So it takes hard skills and soft skills as a whole so that people can adapt to these changes. Science learning at the elementary level plays an important role in equipping students with soft skills in the era of society 5.0. The purpose of this study was to determine the urgency of soft skill development through science learning in SD/MI in the era of society 5.0. The benefit obtained from this research is that it can be a reference for academics and related scientific literacy sources. This study uses a descriptive qualitative approach that emphasizes the phenomenological elements. Methods of data analysis using descriptive analysis method. In this case, data were collected from various sources and then analyzed using descriptive analysis methods.The results of the study indicate that soft skills are skills that must be developed starting from the basic level. Soft skills that must be possessed by students in the era of society 5.0 are leadership, communication, literacy. The development of these soft skills can be implemented through elementary/MI science learning using problem-based learning models, project-based learning, inquiry and discovery learning.